IMPLEMENTATION OF MULTIPLE INTELLIGENCE DEVELOPMENT METHOD IN FIQH LEARNING IN MADRASAH TSANAWIYAH (MTs) - Sapiudin Shidiq; Ahmad Nasuki (Al Qalam, 2021)
Method of applying contemporary fiqh learning is still conventional. This research has purpose to describe method of applying fiqh learning effectiveness in MTs. This research uses a qualitative-descriptive and naturalistic approach by means of interview, observation and documentation instrument. By means of triangulation of data collection and tabulation technique, obtained a research outcome that implementation of fiqh learning method in MTs Pembangunan UIN Jakarta is proportionally considered effective in developing the students multiple intelligence. This is proofed by some implementations of learning method. 1). Movie learning method is effective for student who has talent of music, linguistic and visual-spatial intelligence, 2). Question-answer method is effective for student who has talent of math and logic, 3). Demonstration is effective for student who has talent of kinesthetic-bodily and interpersonal intelligence, 4). Concept chart method is effective for student who has talent of visual-spatial and intrapersonal intelligence. This research can be a model of method application in fiqh learning at MTs.